HUBUNGAN TINGGI BADAN ANAK BARU MASUK SEKOLAH (TBABS) DENGAN KADAR TIROKSIN SERUM DI DAERAH ENDEMIS GAKY KABUPATEN GUNUNG KIDUL DIY - , Atik Juniarsih, kepadaProf. Dr. dr. Djauhar Ismail, MPH, Ph.D, SpA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Iodine deficiency disorderis a set ofsymptoms that is effect the body have continuously iodinedeficiencyin a long time. Organresponsible formanaging theiodineisthe thyroid gland. The thyroid gland produces thyroid hormones, which are found in significant amounts is thyroxine. Thyroid dysfunctioncausesthe body'sgrowth rate will be disruptedandevenstoppedmakingthe bodylook short (stunted). Objective: This study aimsto determine the relationshipbetween the new student body height(TBABS) withthyrosineserum levels iniodine deficiency endemic areaof Gunung Kidul District. Method: The study design was cross sectional with 56 subjects consisted of student Class 1 of Elementary School Planjan 1, Planjan 2 and Kanigoro 1 in Saptosari Subdistrict during period of June 2012. Thebody height was measured using microtoise and thyroxin serum level was examinated with ELISA method. Statistic analysis using bivariate analyisis with fischer exact test and linear regression test to find of the correlation. Results: There were 56 subjects thatconsisted of 31 (55,4%) boys and 25 (44,6%) girls and the mean z score of body height of boys was-1,8 and girls was-1,7.Classification of subject based on the body height were 35 (62,5%) subjectswere normal, 18 (32,1%) subjectswerestunted and 3 (5,4%) subjects wereseverely stunted. Children that werestunted classification if correlated with BMI scale, 4% were underweight, 27% were normal, 5% were overweight and 2% were obese. The blood tests showed that 8 (14,3%) subjects with thyroxine serum level less than 0,8 Î¼IU/dlwere stunted and there was no children with thyroxine serum level greaterthan 2,0 Î¼IU/dl. Children with normal thyroxine serum level, 13 (23,2%) were stunted and 35 (62,5%) were normal. Fischer test result showed that the the body height of school children have correlation with thyroxine serum level (p<0,001, R= 3,692